The functional and semantic plurality of building (fael) in the Arabic language (Journal of the College of Basic Education, 2023)
This research deals with the (subject) construct, which is called in grammar books as (the subject's noun) (1).A building with multiple functions and multiple meanings in systems, and the multiplicity in function and significance of a single building isOne of the reasons for the richness of the Arabic language.It is a common construction between the nominative and the actual, in the sense that this construction comes as a noun in some cases.Adjectives come in verbs in other systems, and they have formal characteristics similar to nouns. These characteristicscollected by Ibn Malik in his statement:(Baljar, Tanween, Al-Nada and AlAnd a predicate for the noun is distinguished with (2)It comes in the systems preceded by the letters called (prepositions), towards: What a◌ leader of his people, and I am amazed at a sinner who does not repent, and comes in addition, like: Zayd who takes what is due, and comes with blessings.Towards: Zaid is standing, and I am writing a letter, and a herald comes, towards: O drowned savior, and it comes connected to(Al), towards: Zayd is the next, and he comes with a support to him, towards the one who takes his right, is respected, and repents the penitent.Therefore, a group of grammarians deluded its external form, so they considered it a name, and they only authorized its effectiveness.under conditions that narrowed the limits of its action, and did not include it with the past tense and the present tense as an apportionment.Third, they are effective in many of their uses.And if the sculptors (the visuals) had narrowed the limits of the actuality of this building and prevailed over them, and a stairway incurricula and schools, the grammarians (Al-Kufin) actually counted it, and called it (the permanent verb), so the mouse says